Dacetuzumab plus rituximab, ifosfamide, carboplatin and etoposide as salvage therapy for patients with diffuse large B-cell lymphoma relapsing after rituximab, cyclophosphamide, doxorubicin, vincristine and prednisolone: a randomized, double-blind, placebo-controlled phase 2b trial. Issue 9 (2nd September 2015) - Fayad, Luis; Ansell, Stephen M.; Advani, Ranjana; Coiffier, Bertrand; Stuart, Robert; Bartlett, Nancy L.; Forero-Torres, Andres; Kuliczkowski, Kazimierz; Belada, David; Ng, Edmund; Drachman, Jonathan G.
Abstract : Single-agent dacetuzumab has demonstrated antitumor activity in relapsed/refractory diffuse large B-cell lymphoma (DLBCL). Preclinical data demonstrated improved dacetuzumab antitumor activity in combination with rituximab, ± chemotherapy. We designed a phase 2b, double-blind, placebo-controlled trial to compare rituximab, ifosfamide, carboplatin and etoposide (R-ICE) + dacetuzumab with R-ICE + placebo in patients with DLBCL who relapsed after rituximab, cyclophosphamide, doxorubicin, vincristine and prednisolone (R-CHOP) (ClinicalTrials.gov #NCT00529503). The primary endpoint was complete response (CR); additional endpoints included failure-free survival and overall survival (OS). Overall, 151 patients were randomized (75 dacetuzumab, 76 placebo). No notable differences between arms in demographics or subsequent treatment parameters were observed. Cytopenias, cough and infection were more frequent with dacetuzumab. Futility analysis failed to demonstrate higher CR rates with dacetuzumab (36% dacetuzumab, 42% placebo); consequently, enrollment was stopped. Unplanned post hoc analysis showed that patients who underwent subsequent autologous stem cell transplant experienced improvement in OS (hazard ratio = 0.195, p = 0.004), which may be explained by potential immunomodulatory effects of dacetuzumab on antigen-presenting cells.